Agricultural Land-based Functional Model for Effective Rural Land Management in Türkiye - Orhan Ercan (Journal of Agricultural Sciences)
Rapid urbanization and industrial expansion exert escalating pressure on rural areas, resulting in the inappropriate utilization of agricultural lands for non-farming purposes. This misuse is notably prevalent across industry, urban development, tourism, mining, and transportation infrastructure sectors. The challenges associated with this issue include land fragmentation, the underutilization of agricultural lands, a lack of effective agricultural land-use planning, identification and reclamation of abandoned agricultural lands, improvement of land acquisition and banking practices, land consolidation, land valuation, digitalization in agriculture, and the imperative for effective governance. In this study, agricultural land management in Türkiye was evaluated from legal, technical, and managerial aspects, and the article proposes a functional model based on agricultural land that integrates rural land management into a broad framework of land policy and agricultural land-use planning. This model encompasses components related to land ownership, value, use, development, and spatial data infrastructure. Successful implementation necessitates the restructuring of existing institutions or the establishment of new ones. This study aims to address the above-mentioned issues and, with the proposed model, achieve a sustainable agricultural infrastructure by resolving the land-based problems of rural areas, and positioning them as a crucial component of rural land management.